Demand for Complementary Financial and Technological Tools for Managing Drought Risk: Evidence from Rice Farmers in Bangladesh - Ward, Patrick S.; Spielman, David J.; Ortega, David L.; Kumar, Neha; Minocha, Sumedha (2015)
Financial and technological innovations that mitigate weather-related production risks have the potential to greatly benefit farmers in many risk-prone. In this study we examine farmers’ preferences for two distinct tools that allow them to manage drought risk: weather index insurance and a recently released drought-tolerant rice variety. We illustrate how these tools can independently address drought risk and demonstrate the additional benefits gained by combining them into a complementary risk management product. Findings indicate that farmers are generally unwilling to adopt the drought-tolerant variety independent of insurance, largely due to a yield penalty under non-drought conditions. When bundled with insurance, however, farmers’ valuation of the variety increases. Farmers value insurance on its own, but even more so when bundled with the drought-tolerant variety. The results provide evidence that farmers value the complementarities inherent in a well-calibrated bundle of risk management tools. Ward, Patrick S.; Spielman, David J.; Ortega, David L.; Kumar, Neha; Minocha, Sumedha